Changes in soil organic carbon under perennial crops. (15th May 2020) - Ledo, Alicia; Smith, Pete; Zerihun, Ayalsew; Whitaker, Jeanette; Vicente‐Vicente, José Luis; Qin, Zhangcai; McNamara, Niall P.; Zinn, Yuri L.; Llorente, Mireia; Liebig, Mark; Kuhnert, Matthias; Dondini, Marta; et al.
Abstract: This study evaluates the dynamics of soil organic carbon (SOC) under perennial crops across the globe. It quantifies the effect of change from annual to perennial crops and the subsequent temporal changes in SOC stocks during the perennial crop cycle. It also presents an empirical model to estimate changes in the SOC content under crops as a function of time, land use, and site characteristics. We used a harmonized global dataset containing paired‐comparison empirical values of SOC and different types of perennial crops (perennial grasses, palms, and woody plants) with different end uses: bioenergy, food, other bio‐products, and short rotation coppice. Salient outcomes include: a 20‐year period encompassing a change from annual to perennial crops led to an average 20% increase in SOC at 0–30 cm (6.0 ± 4.6 Mg/ha gain) and a total 10% increase over the 0–100 cm soil profile (5.7 ± 10.9 Mg/ha). A change from natural pasture to perennial crop decreased SOC stocks by 1% over 0–30 cm (−2.5 ± 4.2 Mg/ha) and 10% over 0–100 cm (−13.6 ± 8.9 Mg/ha). The effect of a land use change from forest to perennial crops did not show significant impacts, probably due to the limited number of plots; but the data indicated that while a 2% increase in SOC was observed at 0–30 cm (16.81 ± 55.1 Mg/ha), a decrease in 24% was observed at 30–100 cm (−40.1 ± 16.8 Mg/ha). Perennial crops generally accumulate SOC through time, especially woody crops; and temperature was the main driver explaining differences in SOC dynamics, followed by crop age, soil bulk density, clay content, and depth. We present empirical evidence showing that the FAO perennialization strategy is reasonable, underscoring the role of perennial crops as a useful component of climate change mitigation strategies. Abstract : This global study shows that a change from annual to perennial crop leads to an increase in soil organic carbon (SOC) while a change from grassland or forest has the opposite effect. Perennial crops, especially woody crops, accumulate organic carbon in the soil through time. Temperature is the main driver explaining differences in SOC dynamics around the world. Perennial crops under current management can be a feasible climate change mitigation option.